Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Hello,
3842
Step-by-step explanation:
[tex]a=4-\sqrt{15} \\\\\dfrac{1}{a} =\dfrac{1}{4-\sqrt{15}} \\\\=\dfrac{4+\sqrt{15}}{(4-\sqrt{15})*(4+\sqrt{15})}\\\\=\dfrac{4+\sqrt{15}}{16-15} \\\\=4+\sqrt{15}\\\\[/tex]
[tex]a+\dfrac{1}{a} =4-\sqrt{15}+4+\sqrt{15}=8\\\\[/tex]
[tex](a+\dfrac{1}{a} )^2=a^2+\dfrac{1}{a^2} +2\\\\a^2+\dfrac{1}{a^2} =8^2-2=62\\[/tex]
[tex](a+\dfrac{1}{a} )^3=a^3+\dfrac{1}{a^3} +3*\dfrac{a^2}{a} +3*\dfrac{a}{a^2} \\\\8^3=a^3+\dfrac{1}{a^3} +3(a+\dfrac{1}{a} )\\\\a^3+\dfrac{1}{a^3} =8^3-3*8=488\\[/tex]
[tex](a+\dfrac{1}{a} )^4=a^4+\dfrac{1}{a^4} +4*\dfrac{a^3}{a} +6*\dfrac{a^2}{a^2} +4*\dfrac{a}{a^3}\\\\a^4+\dfrac{1}{a^4}=(a+\dfrac{1}{a} )^4-4*a^2-4*\dfrac{1}{a^2} -6\\a^4+\dfrac{1}{a^4} =8^4-4*62-6\\\\=4096-248-6\\\\=3842\\\boxed{a^4+\dfrac{1}{a^4} =3842}\\[/tex]
Using a calculator:
[tex]a=4-\sqrt{15}=0,1270166537925831148207346002176....\\\\a^4= 2,6028112122495108436170792979303e-4\\\\\dfrac{1}{a} =4+\sqrt{15} =7,8729833462074168851792653997824...\\\\\dfrac{1}{a^4}=3841,9997397188787750489156382921....\\\\a^4+\dfrac{1}{a^4} \\\\= 2,6028112122495108436170792979303e-4+3841,9997397188787750489156382921....\\\\=3842\\[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.